Correlating 13C Isotope in Oligomeric Proanthocyanidins with their Anticancer Properties - Reginald B. Little; Orit Uziel (Journal of Cancer Genetics And Biomarkers, 2022)
Upon considering the anticancer effects of larger oligomeric proanthocyanidins and observing various papers reporting the high resolution mass spectroscopy of the oligomeric proanthocyanidins, it is determined that the unusual 13C enrichment in some plant oligomeric proanthocyanidins may be responsible for the anticancer activities of these food products. Such correlation of the 13C in the oligomeric proanthocyanidins also correlate with their scavenging of free-radicals, anti-virial and anti-bacterial properties. Proanthocyanidins in grape seeds are observed to have high enrichment in heavy isotopes of 2H, 13C, 15N and/or 17O. Mass analysis of DNA from human cancer cells are compared to normal human cells and cancer cells show bond specific enrichment of heavy isotopes in nucleotides G, A, T and C. On such basis, this study suggests possible stronger interactions of proanthocyanidins with DNA in cancer verses DNA in normal cells due to heavy isotope bond specific enrichments in both proanthocyanidins and the cancer DNA. Such 13C interactions from oligomeric proanthocyanidins with nucleic acids and proteins involved in replications, transcriptions and translations in cancer cells for interacting and chemically altering anabolism and cell division of the cancer cells are consistent with the author’s mechanism for normal cell to cancer cell transformations via possible replacements of primordial 1H, 12C, 14N, 16O, and 24Mg isotopes by nonprimordial 2H, 13C, 15N, and 17O and 25Mg isotopes in the proteins and nucleic acids. Such is also consistent with the proposed treatment for cancer by the author by use of foods containing proteins, nucleic acids, carbohydrates and/or drug molecules enriched with the nonprimordial isotopes of 2H, 13C, 15N, and 17O and 25Mg.
Keywords: Cancer